Analisis Penerapan Sistem Penataan Arsip Konvensional Pada Kantor PN - Amelinda, Rike; Wolor, Christian Wiradendi; Adha, Maulana Amirul (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2023)
Conventional Archives are Archives whose information is recorded on Paper Media in the form of handwriting or typing. Archives are a very important part of Office Work, because written information must be accurate and available when needed. Archives Management System is an activity of organizing and compiling Archives in a systematic order, as well as storing and caring Archives for safe and economical use. This Research aims to find out Conventional Archives Management System at the PN Office, especially Bureau of Human Resources and General Affairs Sub-Section of Archives. Researcher used case study qualitative research and data collection technique using observation, interview, and documentation. The Results of the Research explained that Employees had difficulty finding Archives again, because they found Old Archives that were no longer needed but had not destroyed Archives.